Đào tạo kiến thức số cho sinh viên trong thư viện đại học - Ngô, Thanh Thảo (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The article provides overview on digital knowledge and digital knowledge training for students at university libraries in the world, then recommends the contents and methodologies of digital knowledge training at university libraries in Vietnam.